The Match-up hypothesis under a social class perspective - Silva, João Bernardo Faia do Jogo Ribeiro da (2018)
Purpose – The Match-up hypothesis is a concept which suggests that the stronger the match (i.e. the congruence, adequacy), between both a celebrity and a product, the more effective an endorsement will be. In this paper, we pretend to examine the mentioned match-up hypothesis under a social class perspective. Design/Methodology – An experiment, consisting of two surveys, was conducted to evaluate both the perceived adequacy of a celebrity-product match and its impact on consumers’ purchase intentions. Findings – Results revealed that, although the match enhanced consumer’s perceived adequacy, this rise was not translated into greater purchase intentions. Research limitations – The usage of only one product category, as well as differences regarding personal preferences and biases stemming from the non-probabilistic sampling method, were some of the limitations faced during the research. In addition, the lack of information about the topic, since it had never been studied, corresponded to another limitation. Practical implications – By acknowledging that consumers do perceive an adequacy and match between the type of products and the celebrities’ social class, companies, through their marketing and communication departments, are able to create, design and “shape” specific strategies in order to increase both the effectiveness of endorsements and consumers’’ engagement. Social implications – As a result of its marketing nature and company specific focus, the present research does not offer a wide spectrum of social implications. However, one might consider the understanding of an existing cognitive association, as well as a mental construct, between consumers’ minds and the social characteristics of the elements involved in a consumption decision as a major contribution in this field. Originality - Extant literature has only focused on the celebrity’s attractiveness (physical and/or intellectual) and credibility (expertness and trustworthiness), being the present work the first to focus and explore other perspectives and characteristics such as the social class.